Site Fidelity, Home Range Size and Movement Patterns of a Mega-Fish, Luciobarbus esocinus, in Keban Reservoir, Euphrates River - Alp, Ahmet; Akyuz, Adil; Gunduz, Fatih; Demirol, Ferhat; Coban, Mehmet zulfu; Yuksel, Fahrettin; Yerli, Sedat vahdet (Wiley, 2025)
Luciobarbus esocinus (mangar), a critically endangered mega-fish species (<= 140 kg) endemic to the Euphrates and Tigris river systems, faces severe threats due to habitat fragmentation. To assess its spatial ecology in the Keban Reservoir, 30 individuals were acoustically tagged and monitored for 218-437 days using 18 receivers deployed in the reservoir. The tagged fish exhibited low site fidelity, with station residency indices (RI) ranging from 0.00 to 0.46 and detection periods lasting 59-153 days. Depth and temperature data (115,318 and 112,789 records, respectively) revealed seasonal habitat shifts: individuals occupied deeper waters in winter (mean 10.1 m), shallower depths in spring (4.4 m) and summer (3.8 m), and tolerated temperatures of 7.4 degrees C-28.4 degrees C. Although depth use was weakly correlated with temperature, trends indicated shallower occupancy during warmer periods. Home range analyses showed a maximum linear home range (LHR) of 36.5 km and the areal home range estimated via minimum convex polygon (MCP) was 6422.8 ha. In addition, kernel density (KD) analysis revealed the 95% KD area was 2877.0 ha, the 75% KD area was 67.7 ha and the 50% KD area was 33.8 ha. Seasonal migrations spanned 25-30 km upstream/downstream from release sites, particularly toward tributaries in spring. Around the Keban Reservoir, 14 hydroelectric power plants (HPPs) present and most of these HPP are not designed suitable fish passages. Urgent conservation measures are needed, including Fish Conservation Zones in critical habitats and connectivity restoration via functional fishways, to safeguard this imperilled species in fragmented river-reservoir ecosystems.
Keywords: acoustic telemetry; home range; Luciobarbus esocinus; mega-fish; movement ecology